Morant Bay, Jamaica 1865 - Hall, D. G. (My University, 1955)
Manuscript of Morant Bay, Jamaica
28 pgs. Typescript, letter-sized, sepia-toned, good condition.
Keywords: Jamaica - History - Morant Bay rebellion 1865-1866.; Jamaica - History - Insurrection 1865